2013
DOI: 10.1128/jvi.02030-12
|View full text |Cite
|
Sign up to set email alerts
|

The West Nile Virus Capsid Protein Blocks Apoptosis through a Phosphatidylinositol 3-Kinase-Dependent Mechanism

Abstract: West Nile virus (WNV) is a mosquito-transmitted pathogen that can cause serious disease in humans. Our laboratories are focused on understanding how interactions between WNV proteins and host cells contribute to virus replication and pathogenesis. WNV replication is relatively slow, and on the basis of earlier studies, the virus appears to activate survival pathways that delay host cell death during virus replication. The WNV capsid is the first viral protein produced in infected cells; however, its role in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 55 publications
2
54
0
1
Order By: Relevance
“…It was recently found that WNV capsid induces PI3 kinase-dependent activation of Akt by phosphorylation at S473 and that Akt activation was found to delay WNVinduced caspase-3-dependent apoptosis (36). We evaluated the role of S473 phosphorylation on Akt by mTOR in our rictor knockout studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently found that WNV capsid induces PI3 kinase-dependent activation of Akt by phosphorylation at S473 and that Akt activation was found to delay WNVinduced caspase-3-dependent apoptosis (36). We evaluated the role of S473 phosphorylation on Akt by mTOR in our rictor knockout studies.…”
Section: Discussionmentioning
confidence: 99%
“…Flavivirus endocytosis transiently activates Akt through a PI3K-dependent mechanism that can be detected as early as 1 h postinfection (33)(34)(35)(36) and therefore may be important in activating p70S6K in support of viral gene expression. To determine the significance of WNV-induced mTOR- (UV-WNV).…”
Section: Wnv Activates Mtormentioning
confidence: 99%
“…Production of polyclonal antibodies to the amino-terminal 20 amino acid residues of DENV-2 capsid protein in guinea pigs was contracted to Pocono Rabbit Farm and Laboratory (Canadensis, PA). Guinea pig and rabbit polyclonal antibodies to WNV capsid protein and goat anti-p32 were generated in our laboratory (2,12,13). Rabbit polyclonal antibodies to the tripeptide Ser-Lys-Leu (SKL) were produced as described previously (14).…”
Section: Methodsmentioning
confidence: 99%
“…Bound immune complexes were washed several times with NP-40 lysis buffer before elution by boiling in protein sample buffer. Proteins were separated by SDS-PAGE and transferred to polyvinylidene difluoride (PVDF) membranes for immunoblotting, as described previously (2). Confocal and superresolution microscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation